خصائص اللغة العربية في خدمة الاصطلاح العلميّ (نماذج من كتاب "القانون في الطبّ" لابن سينا) - جباري, سارة; برباق, ربيعة (جامعة الوادي - University of Eloued, 2020)
ملخص: تعتمد عملية الاصطلاح العلميّ في اللغة العربية على آليات ووسائل وشروط خاصّة، تتولّد من خلالها مادّة لغوية ومعرفة خاصة ذات معاملة تأثير في المدوّنات المنتمية لاختصاص واحد. وإذا عقدنا ربط الصلات بين هذه الآليات وبين خصائص اللغة العربية وجدنا قواسم مشتركة كبرى تؤكّد خدمة خصائص اللغة العربية لعملية الاصطلاح العلمي، وفيما يلي وقفة نظرية وعملية لاكتشاف مدى هذا التطابق. Abstract: The process of scientific reform in the Arabic language depends on mechanisms، mean ans special conditions through which a special linguistic and cognitive material are generated with a coefficient influence on blogs belonging to one speciality. And if we make a link between، the mechanisms and the characteristics (properties) of the language; we will found out several common denominators that confirm the Arabic language characteristics in serving the scientific reform; and here is a theoretical and practical pause to discover the extent of this congruence
مقال
Keywords: خصائص اللغة ; علم الاصطلاح ; المصطلح العلمي ; الإنتاج المصطلحي ; التوافق العلمي; anguage characteristics ; terminology ; scientific term ; terminology production ; scientific compatibility